The Impact of Word-Touch Synchrony on Early Language Development: Preliminary Findings From Korean Mother-Child Interactions. - Jongmin Jung; Eon-Suk Ko (Journal of Speech, Language & Hearing Research, 2025)
Purpose: This study evaluates the impact of temporal synchrony between maternal touch and speech on children's early language development. It investigates whether the proportion of word-touch co-occurrence, overlap, and alignment precision in maternal input influences language acquisition, hypothesizing that such synchrony boosts infants' attention and aids speech segmentation. Method: We analyzed video recordings of 21 infants aged 6-16 months (Mage = 10 months 21 days, SD = 3 months 1 day), focusing on 6 min of interaction data per mother-infant pair. This age range marks a stage of development where infants are in the process of learning to segment words and associate them with meanings, highlighting their potential to benefit from redundant multimodal cues. The analysis included frequency of word-touch cooccurrence, extent of overlap, and precision of alignment. Infants' language skills were assessed using the Sequenced Language Scale for Infants (Kim, 2002), a standardized parent-report scale designed to evaluate language development in Korean infants. Results: Multivariable linear regression analyses indicated that higher proportions of word-touch co-occurrence and overlap, along with more precise alignment, positively correlated with infants' receptive language scores but did not significantly affect expressive language outcomes. Conclusion: The findings underscore the significant role of temporal synchrony between maternal touch and speech in enhancing infants' receptive language skills.